Top-down vs bottom-up processes: A systematic review clarifying roles and patterns of interactions in food system transformation - Conti, Costanza; Hall, Andy; Moallemi, Enayat A.; Laila, Amar; Bene, Christophe; Fanzo, Jessica; Gibson, Matthew Ford; Gordon, Line; Hicks, Christina; Kok, Kristiaan; Rao, Nitya; Laxminarayan, Ramanan; et al. (Elsevier, 2025)
Urgent calls for food system transformation have spurred a variety of responses globally. In some cases, these calls have been answered through top-down led processes, driven by public agencies to design and implement measures that can drive societies towards more viable patterns of development. In other cases, transformation processes have been ignited by community level actors who addressed sustainability issues with context-specific solutions. The broad range of actors raises the question of whether it is top-down or bottom-up processes and actors that are better placed to deliver the fundamental and system level changes that characterise transformation. Through a systematic review, we identified 40 case studies across 24 countries to investigate the role of top-down or bottom-up processes in transformation, whether the two might intertwine, and with what results. We propose five different types of interactions: Autonomous Bottom-Up, Collaborative Bottom-Up, Top-Down Struggles and Resourceful Bottom-Up, Collaborative Top-Down and Transformation Alliances. Based on our analysis, we propose a new heuristic of roles and interactions between different actors. We suggest a shift from dichotomic views on top-down and bottom-up actor roles towards the concept of “transformation functions,” which would re-centre the discussion around the existing or needed capabilities for transformation in different contexts. Finally, we call for further research to determine how different transformation functions need to become more synchronised -or coordinated-to accelerate transformation.